Comprehensive determination of ground motion parameters based on Matlab - Lei Shao; Gang Hu (地震科学进展, 2024)
This paper mainly introduces a program written in Matlab for determining ground motion parameters. From the three framework modules of input, processing and output, the author combines his understanding and experience to analyze the process of determining design seismic parameters in detail. It uses an Excel file to control the input parameters as a whole, taking into account factors such as peak ground acceleration, site classification, design earthquake grouping, and zoning map adjustment factors. It simplifies the complex process of processing response spectrum data, and achieves automatic calibration of borehole response spectra under different standard spectra recommended by different codes, automatic saving of maps, and exporting of ground motion parameter tables. The program can comprehensively analyze multiple boreholes and multiple response spectrum data for different design reference periods and different probability levels of exceedance at one time, which is very efficient in handling regional seismic safety evaluation and other multi-site engineering projects. The application analysis of examples in seismic safety evaluation work is also presented in the article. The program can not only process bedrock response spectrum, but also analyze the overall or individual response spectrum of boreholes to obtain more reasonable ground motion parameters, which is helpful for the seismic safety evaluation work.